Potential Use of Mosquito’s Salivary Components as Novel Target for The Development of Transmission Blocking Vaccine (TBV) - KARTIKA SENJARINI (Indonesian Society for microbiology, 2013)
Mosquito-borne diseases are rampant in most tropical regions of the world, especially rural, forested, and coastal areas such as Indonesia. Despite long-standing chemotherapeutic intercession and vector control programs, mosquito-borne diseases exact a heavy burden on human health in Indonesia. Two major public health problems transmitted by mosquito in Indonesia are malaria and dengue haemorrhagic fever (DHF), causing millions of clinical episodes occurring annually. Malaria is now recognized as a serious re-emerging threat to public health. DHF cases were first observed in 1968; since then, the incidence has been constantly increasing and the disease is now one of the principal causes of child lethality. It has been widely observed that saliva of mosquito that transmits the diseases contains several factors that could enhance pathogen infection. Therefore, it should be possible to control pathogen transmission by vaccinating the host against the molecule(s) in saliva that potentiate the infection. However, specific component as a potential target for TBV in mosquito vectors of malaria & dengue, i.e. Anopheles and Aedes aegypti, has not been identified so far. This paper wanted to elaborate the potential role of salivary component from mosquitoes, particularly from Indonesian vectors as molecular target for developing TBV against two major Mosquito borne-diseases in Indonesia i.e. malaria and DHF.